Influence of human factors on organisational performance Quality improvement practices as a mediator variable - Habtoor, N (Emerald Group Publishing Ltd, 2024)
Purpose - The purpose of this paper is to explore the influence of human factors in quality management on quality improvement practices and organisational performance in the Yemeni industrial sector. Design/methodology/approach - Data were collected via a quantitative survey with a questionnaire distributed to 261 managers from 87 industrial companies. Replies from 210 managers give a response rate of 80 per cent. Data were analysed with Statistical Package for the Social Sciences 16.0, including factor analysis, reliability analysis, descriptive statistics, and correlation analysis. Structural equation modelling was carried out using Amos to evaluate the model and hypotheses. Findings - Human factors influence positively quality improvement practices and organisational performance. Quality improvement practices positively influence organisational performance. Human factors indirectly and significantly influence organisational performance via the mediator of quality improvement practices. Research limitations/implications - The findings will be useful to both researchers and managers, especially those in Yemeni industrial companies. For further work, this study can be expanded to cover companies in other Middle East countries, and it may include more human factors. Originality/value - The study is one of a few that investigate the influence of human factors on quality management. Additionally, this study is the first to carry out such research in the Yemen and the Middle East region.